Augmented reality in the context of universal design for hearing impaired student - Luangrungruang, Tidarat; Phatai, Gawalee (Institute of Advanced Engineering and Science, 2025)
Advancing equal rights and prohibiting discrimination based on disability are essential to achieving social equity. Education serves as a vital mechanism in this effort, particularly through inclusive practices that support diverse learners. Sakon Nakhon Rajabhat University advances these values by admitting students with disabilities, including those with hearing impairments, and by fostering accessible learning environments. This study presents the development of an augmented reality (AR) application, designed according to universal design (UD) principles, to enhance learning for students with hearing impairments. The AR technology integrates real and virtual elements to create an engaging and interactive educational experience. Evaluation results indicate a high level of effectiveness, with the assessment dimension receiving the highest mean score (? = 4.87, ?? = 0.35), and overall effectiveness rated similarly (? = 4.78, ?? = 0.42). User satisfaction was also rated at a very high level across all aspects (? = 4.67, ?? = 0.54). These findings highlight the potential of AR technology, when guided by inclusive design principles, to improve learning outcomes for students with hearing impairments.